Towards a framework to measure knowledge transfer in organizations - Binti Mohamad Sani, N.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Knowledge transfer has become a common initiative in organizations to share knowledge. However, the act of measuring knowledge transfer is rarely being measured by the organizations. This is due to the fact that there are lacks of guidelines such as model or framework to measure the process of knowledge transfer. Therefore, the main objective of this study is to adopt a framework (HOT-fit) that could guide practitioners in measuring knowledge transfer with the presence of information technology (IT) as an enabler. Significantly, this study will explore how technology would be impactful in the process of knowledge transfer. In the process of coming out with the adopted proposed framework, a deep literature studies into previous works have been conducted. Since the HOT-fit evaluation framework were firstly proposed and experimented for the Health Information System (HIS), this study is focusing on extending the work by Maryati et. al into another perspective which is Knowledge Management System (KMS) specifically in knowledge transfer processes. The three fit factors which are human, organizational and technology have been brought into different view and being interpret in terms of knowledge transfer process accordingly. Results from this literature studies will lead to a proposed framework that could be used for measuring knowledge transfer practices. The adopted framework will then be assessed by conducting case study in selected organizations that implement Knowledge Management initiatives. The findings of this research will be significant to organizations in determining the strengths and weaknesses of their knowledge transfer practices as well as to be able to conduct it effectively with the support of current technologies. Â© 2015 IEEE.